Teachers’ Challenges and Readiness of the School on the Implementation of Expanded Face-to-face Classes - Yambot, Rowel L; Ayro, Eufemia C; Vidal Jr, Efraim S (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study investigated the teachers ‘challenges in implementing expanded face-to-face classes and school standards and procedures in the Division of Nueva Ecija. This utilized descriptive research in describing the socio-demographic profile of the respondents as well as their perceived student attitudes towards learning Araling Panlipunan, challenges on the implementation of face-to-faces and perception of school standards and procedures. A total of 48 teachers were selected purposively as respondents to the study. They were teachers in Carranglan District handling Araling Panlipunan subjects in the Schools Division of Nueva Ecija. The survey questionnaire was administered. Data gathered were analyzed using frequency, mean and percentage. Meanwhile, Chi-square was used to establish relationships among variables. The study shows that regular monitoring of students’ performance through their assessments and performance tasks ranks first as issues and challenges that Araling Panlipunan teachers experienced during the pandemic, and resiliency and flexibility were the traits that the respondents described. With the study’s findings, an intervention plan is proposed to help Araling Panlipunan teachers overcome the challenges in teaching and attain their full potential. This will become the basis for educators and administrators to help them enhance their competencies in the field.